Comparison Of Wakalah And Kafalah In The Implementation Of Sharia Finance - Ahmad Ibrohim (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
Wakalah in the sense of submission, delegation, or giving a mandate is also found in the word Al-hifzhu which means maintenance. Therefore, the use of the word wakalah or wikalah is considered to have the same meaning as hifzhun. In the business world, everyone has different competencies. There are times when people have competence in a competitive business field but do not have capital. On the other hand, there are capital owners who do not have the time or are less competitive in the field, so they need a business partner with a representative pattern. Representing work that you can do yourself is considered valid according to sharia. Such as buying and selling, marriage, thalaq, membership, pawning and others related to muamalat. Representing something related to worship, there are some jobs that are permissible and there are some that are not permissible according to sharia'.